ANALISIS MODEL KEPEMIMPINAN YANG MENDUKUNG PROFESIONALITAS GURU PENDIDIKAN ANAK USIA DINI (PAUD) DI KOTA SURABAYA: ANALYSIS OF LEADERSHIP MODELS TO SUPPORT PROFESSIONALITY OF EARLY CHILD EDUCATION TEACHERS IN SURABAYA CITY - ANITA MAULIYAH (incrementapedia, 2023)
Professional teachers become an illustration of the ability of a teacher to determine the direction of goals, values and quality in teaching in accordance with their competence in administering education. Teacher professionalism is seen as having a relationship with leadership models, especially in early childhood education (PAUD), both formal and non-formal education. This study aims to analyze the ideal leadership model seen as capable of supporting teacher professionalism from the perspective of PAUD teachers in Surabaya. This research using descriptive quantitative method collected primary data using questionnaires and the Thurstone scale model which was distributed to 184 PAUD teachers, both in Kindergarten (TK) and Groups of students (KB). The analysis technique was carried out using the K-Mean Cluster to describe a group of teachers based on an ideal leadership perspective. The results of the cluster analysis grouped 27% of teachers with a transformational leadership perspective, 41% of teachers with a democratic leadership perspective, and 32% of teachers with a charismatic leadership perspective. The results of the inferential analysis that tested the correlation between the leadership model and teacher professional development obtained a value of ꭓ2 of 72.095 at p=0.000 (p<0.05) which proves that the leadership model perspective has a significant correlation with teacher professional development. An important finding in this study is that teachers' educational background has no correlation with their professionalism, while the factors of teacher age, number of students, and teacher tenure have a significant correlation with PAUD teacher professionalism. It is suggested that each PAUD educational institution should develop strengths in each leadership character which is seen as able to support teacher professionalism, namely by providing support for efforts to develop teacher potential by increasing supervision, providing training and supporting the learning process.